Mechanisms of micro-terror? Early career CMS academics' experiences of 'targets and terror' in contemporary business schools. Issue 4 (September 2020) - Ratle, Olivier; Robinson, Sarah; Bristow, Alexandra; Kerr, Ron
In this article, we apply the concept of 'targets and terror', previously used in the healthcare sector, to the audit culture within business schools. We explore to what extent terror, or the inculcation of fear through processes of domination, is identifiable in the micro-level experiences of early career academics. Drawing on an international study of 38 Critical Management Studies early career academics from 15 countries, we develop a theoretical framework combining Bourdieu's modes of domination and Meyerson and Scully's Tempered Radicalism, which helps us identify top-down and horizontal processes of micro-terror and bottom-up processes of micro-terrorism, specifically self-terrorisation and counter-terrorisation. In extending the study of 'targets and terror' cultures to contemporary business schools, we develop a clearer understanding of how domination plays out in the everyday processes of management and self-management. From Bourdieu's modes of domination, we discern a dark picture of institutional and interpersonal overt and symbolic violence in the name of target achievement. The Tempered Radicalism lens helps us to understand early career academic challenges that can lead to self-terrorisation but also brings possible ways forward, showing early career academics how to resist mechanisms of micro-terror through their own small acts of counter-terrorisation, providing some hope specifically as the basis for collective resistance.